Arendt y Santo Tomás : mal, ignorancia e irreflexión - Susnik, Martín (Sapientia, 2018)
This article aims to describe the Hannah Arendt´s thesis of “banality of evil”, that she proposed after Adolf Eichmann´s trial, and compare it with the doctrine of Saint Thomas Aquinas about the causality of moral evil –especially from an anthropologic-psychologic point of view–, as he develops it in Summa Theologiae. After exposing the main thesis of both authors, we seek to mark some common grounds, their differences and the possible mutual enrichment between them.